![if \: (a + b + c)(a - b + c ) = {a}^{2} + {b}^{2} + {c}^{2} .then \: sow \: that \: a \: b \: c \: are \: in \: continued \: proportion if \: (a + b + c)(a - b + c ) = {a}^{2} + {b}^{2} + {c}^{2} .then \: sow \: that \: a \: b \: c \: are \: in \: continued \: proportion](https://tex.z-dn.net/?f=if+%5C%3A+%28a+%2B+b+%2B+c%29%28a+-+b+%2B+c+%29+%3D++%7Ba%7D%5E%7B2%7D++%2B++%7Bb%7D%5E%7B2%7D++%2B++%7Bc%7D%5E%7B2%7D+.then+%5C%3A+sow+%5C%3A+that+%5C%3A+a+%5C%3A+b+%5C%3A+c+%5C%3A+are+%5C%3A+in+%5C%3A+continued+%5C%3A+proportion)
Answers
Answered by
20
solutio :-
answer :
Therefore :
a , b , c is in continued proportion.
Answered by
3
Answer:
(a+b+c)(a-b+c)=a2+b2+c2
⇒
(a+c)2-b2=a2+b2+c2
⇒
a2+c2+2ac-b2=a2+b2+c2
⇒
2b2=2ac
⇒
b2=ac
Therefore, a, b, c are in continued proportion.
Explanation:
(a+b+c)(a−b+c)=a
2
+b
2
+c
2
.thensowthatabcareincontinuedproportion
Similar questions